A Comparative Study to Assess the Effect of Balloon Therapy Versus Spirometry in Promotion of Respiratory Function in Children with Lower Respiratory Infection at SMCH - Dr.G.Bhuvaneshwari (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Introduction The respiratory system is a frequent site of illness in children. Respiratory infection and allergies together are responsible for many disruptions in family life and which force them to miss their school work. Most children have 3 to 5 attacks of acute respiratory infection in each year. The respiratory rate is a valuable clinical sign for diagnosingacutelowerrespiratoryinfectioninchildrenwhocoughandbreatherapidly.Blowingballoonsexercises therespiratory muscles, a group of muscle sinteracting to adaptthoracic dimension stocertainbreathingst ages &Aspirometry is a device used for the evaluation of lung function with a spirometer. So the present study is to effectofballoontherapyversusSpirometryinpromotionofrespiratoryfunctioninchildrenwithlowerrespiratory infection at SMCH. Methods Quasi experimental research pretest posttest design was done in SMCH. Totally 60 samples were selected, in that 30 samples were selected for experimental group1 & 30 samples were selected for experimental group II. Purposive Sampling Technique method was used in selecting the samples. Physiological parameters were used to collect data on to assess the effect of balloon therapy versus spirometry in promotion of respiratory function in children with lower respiratory infection. Result It is found that balloon therapy was statistically significant at the level of heart rate and O2 saturation at p<0.05 level between pre and post-test, where the spirometry shows the most significant in the level of respiratory rate when compared to balloon therapy group. Conclusion Educational programs in helping the children by teaching them to regard balloon therapy and incentive spirometry on prevention of respiratory problem, improvement of lung function, reduction of length of hospitalization and repeated hospitalization.